Explorations in second language acquisition and processing - Slabakova, Roumyana; Corbet, James; Domínguez, Laura (Linguist); Dudley, Amber; Wallington, Amy (Cambridge Scholars Publishing Cambridge Scholars Publishing, 2019)
This book presents cutting-edge research on the nature of grammatical systems developed by bilinguals and second language learners, as well as how speakers put these grammatical systems to use in processing language. The chapters provide a stimulating mix of theoretical contributions and experimental designs addressing a variety of research questions, such as learnability and access to Universal Grammar, native language influence, variability, and what propels language development from one stage to the next. Bilingual development is a special highlight here. The linguistic domains investigated are also extremely diverse, and include morphology, syntax, and language processing, as well as the interfaces between syntax and semantics and between syntax and discourse. The book covers the acquisition of an impressive number of languages including Arabic, Croatian, Chinese, English, German, Italian, Japanese, Portuguese, and Spanish as first or second languages. Through these diverse contributions, the reader will be able to identify and follow important new directions in which generative language acquisition is developing and expanding.